Friend Ship Trip to Tell Story of Maritime School - Vallejo Times-Herald (Vallejo Times-Herald)
"The good will voyage of the Golden Bear has accomplished more in familiarizing the people of California with the fact that the California Maritime Academy, located in Vallejo, is a going concern and preparing a selected group of young men for service as officers in the American Merchant Marine, than all previous attempts to publicize the school. These words were employed yesterday noon by Commodore Russell Ihrig, superintendent of the academy in an address before the Rotary Club.